Exploring Postgraduates’ Adoption of AI-Based Tools in Selected Higher Education Institutions in Delta State - Daniel, Reuben; Iteku, Johnson Aborivwighre; Faith, Okose (LP2M Universitas Ibrahimy, 2026)
This study explores Delta State, Nigeria, postgraduates’ knowledge of and engagement with AI-based tools for language learning. This study sought to identify the levels of awareness and different facets of engagement, and the correlation of the two variables amongst the Population of 1000 postgraduates, 870 respondents were selected through stratified random sampling. Participants’ data were obtained through questionnaires, which were later analysed through thematic and descriptive analysis. The results of the study showed a mix of different levels of awareness of tools, with a notable knowledge of, and a lack of awareness of, functionalities like predictive analysis and automated grading. The results of the study indicated that AI-based tools for test preparation, translation, recommendations, and general skill improvement were used in moderate-to-high frequencies. The analysis demonstrated a greater level of awareness of AI-based tools and adoption. The study recommendations include integration of AI-based tools for additional training offered to students, and that curricula designed for Nigerian students be developed. The main conclusion of the study was that awareness is the main influencer. The research offers a postgraduate African context empirical contribution; specifically, the study shows how the components of technology acceptance, awareness, and perceived usefulness are interrelated. Limitations include self-reporting biases and the small geographic scope. Ascertaining the true effect of AI on students' language skills and overall academic achievement lends to future investigations the need for experimental and longitudinal designs.